1995
DOI: 10.1002/ardp.19953280108
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory Activity of Amine‐carboxyboranes in Rodents

Abstract: Amine-carboxyboranes are potent anti-inflammatory agents reducing induced edema and pleural effusion at 8 mg/Kg, i.p. They protect against LPS (Salmonella) induced septic shock from 2-8 mg/Kg/day and are effective in blocking pain mediated both locally and centrally. The mode of action of these agents is by blocking release of cytokines from macrophages, thus reducing lysosomal hydrolytic and proteolytic enzyme activities of affected cells. The agents also reduce prostaglandin and leukotriene synthesis by bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Tricyclohexylphosphine-borane (CyH 3 PBH 3 ) and triphenylphosphine-carboxyborane (Ph 3 PBH 2 COOH), the two most active compounds in this series, inhibited carrageenan-induced edema by 60 and 59%, respectively, in mice at a dose of 8 mg/kg x 2, I.P. In further studies [69], Ph 3 PBH 2 COOH demonstrated potent acute antiinflammatory activity in the rat Winter's and pleurisy tests reducing edema 39% and 72%, respectively. A 51% reduction in edema in the chronic arthritis test was also observed for this compound.…”
Section: Phosphine Boranesmentioning
confidence: 95%
See 1 more Smart Citation
“…Tricyclohexylphosphine-borane (CyH 3 PBH 3 ) and triphenylphosphine-carboxyborane (Ph 3 PBH 2 COOH), the two most active compounds in this series, inhibited carrageenan-induced edema by 60 and 59%, respectively, in mice at a dose of 8 mg/kg x 2, I.P. In further studies [69], Ph 3 PBH 2 COOH demonstrated potent acute antiinflammatory activity in the rat Winter's and pleurisy tests reducing edema 39% and 72%, respectively. A 51% reduction in edema in the chronic arthritis test was also observed for this compound.…”
Section: Phosphine Boranesmentioning
confidence: 95%
“…The phosphine borane affected cytokine levels to a lesser extent, reducing TNF-α, IL-1 and IL-2 levels approximately 35% for each. [69].…”
Section: Phosphine Boranesmentioning
confidence: 95%
“…Reaction with ( þ )-pinanediol then provided the boronic ester (111). The boropeptide (112) was obtained in 80% yield and it was transformed to (113) and (114). DuPont 714 (75) obtained from (114) The asymmetric synthesis of an unprotected a-aminoboronic acid analog of L-arginine (104) and its N-acetyl derivatives (115 and 116) provided alternative substrates or inhibitors of nitric oxide synthase (Scheme 4.23) [80].…”
Section: Synthesis Of Arginine A-aminoboronic Acidsmentioning
confidence: 99%
“…R see in Table 4 Today, many of these molecules are known to possess remarkable antitumor [110,111], antiosteoporotic ( [112] and references therein), anti-inflammatory ( [113] and references therein), and hypolipidemic activities [114], and their mode of action is under investigation [115].…”
Section: Synthesis and Activity Of Amine-carboxyboranes And Their Dermentioning
confidence: 99%
“…o-phenantroline , EDTA, and ferric chloride with drug concentrations at 25, 50, and 100 M measured at 510 n n~'~' ' .…”
Section: F W E Ktrdicul Assay\mentioning
confidence: 99%